Characterization of the complete chloroplast genome of Zingiber zerumbet. Issue 3 (2nd July 2020) - Qi, Huasha; Yun, Yong; Chen, Xuan; Ren, Junfang; Sun, Xiuxiu; Zheng, Daojun
Abstract: Different species of Zingiberaceae are very similar in appearance, which brings some obstacles in the accurate identification of species. Here, we assembled and analyzed the complete chloroplast (cp) genome of Zingiber zerumbet . The cp genome of Z. zerumbet is 169, 183 bp in length, which contains a pair of inverted repeated (IR) regions of 37, 480 bp, a large single copy (LSC) region of 86, 709 bp, and a small single copy (SSC) region of 7, 515 bp. The genome contains a total of 138 genes, including 92 protein-coding genes, 38 transfer RNA genes, and eight ribosomal RNA genes. Phylogenetic analysis exhibited that the cp genome sequence could distinguish Z. zerumbet from other species. This study is beneficial to the germplasm identification and utilization of Z. zerumbet .